2018
DOI: 10.1021/acs.jpcc.7b12140
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Transition Metal Oxide Layered Framework: O3-Type Na[Ni0.32Fe0.13Co0.15Mn0.40]O2 Cathode Material for High-Performance Sodium-Ion Batteries

Abstract: Analogous compounds in lithium-ion batteries (LIBs), various ternary chemical compositions in O3-type layered oxides, have been introduced in sodium-ion batteries (SIBs). However, O3-type ternary transition metal oxide cathodes, including the NaNi x Co y Mn z O 2 and NaNi x Fe y Mn z O 2 (x + y + z = 1) compounds, continue to face several challenges with respect to their low reversible capacity and poor cycle retention owing to their structural instability. Herein, we propose the wellbalanced quaternary transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…To evaluate the overall performance of C-NMNM, a comparison of stability has been made between C-NMNM and other published layered metal oxides in Figures 2E and 2F. During cycling at the 0.5 C (Figure 2E) and 1 C rates (Figure 2F), the capacity retention of C-NMNM is superior to those of the different kinds of P2, O3, and P2/O3-type cathode materials (Yao et al., 2017, Chen et al., 2015, Li et al., 2017, Guo et al., 2015a, Zhang et al., 2016a, Dai et al., 2017, Guo et al., 2017, Yao et al., 2017, Palanisamy et al., 2017, Wang et al., 2017, Gao et al., 2018, Hwang et al., 2018, Risthaus et al., 2018). It is concluded that the cycling lifespan can be dramatically optimized after surface modification.
Figure 2Electrochemical Performance of the P-NMNM and C-NMNM Electrodes(A and B) The charge/discharge profiles (A) at the 0.5 C rate and (B) at the 1 C rate.(C and D) Long-term cycle life and coulombic efficiency for 400 cycles at 0.5 C (C) and 1 C (D).(E and F) Comparison of the capacity retention of C-NMNM electrodes against other cathode materials (E) at the 0.5 C rate11, 18, 23-27, and (F) at the 1 C rate5, 7-9 28, 29.See also Figures S6 and S7.
…”
Section: Resultsmentioning
confidence: 86%
“…To evaluate the overall performance of C-NMNM, a comparison of stability has been made between C-NMNM and other published layered metal oxides in Figures 2E and 2F. During cycling at the 0.5 C (Figure 2E) and 1 C rates (Figure 2F), the capacity retention of C-NMNM is superior to those of the different kinds of P2, O3, and P2/O3-type cathode materials (Yao et al., 2017, Chen et al., 2015, Li et al., 2017, Guo et al., 2015a, Zhang et al., 2016a, Dai et al., 2017, Guo et al., 2017, Yao et al., 2017, Palanisamy et al., 2017, Wang et al., 2017, Gao et al., 2018, Hwang et al., 2018, Risthaus et al., 2018). It is concluded that the cycling lifespan can be dramatically optimized after surface modification.
Figure 2Electrochemical Performance of the P-NMNM and C-NMNM Electrodes(A and B) The charge/discharge profiles (A) at the 0.5 C rate and (B) at the 1 C rate.(C and D) Long-term cycle life and coulombic efficiency for 400 cycles at 0.5 C (C) and 1 C (D).(E and F) Comparison of the capacity retention of C-NMNM electrodes against other cathode materials (E) at the 0.5 C rate11, 18, 23-27, and (F) at the 1 C rate5, 7-9 28, 29.See also Figures S6 and S7.
…”
Section: Resultsmentioning
confidence: 86%
“…Reproduced with permission. [ [104] Copyright 2018, American Chemical Society. e) Diagram of capacity and voltage with energy density curves superimposed for Na x MO 2 with different numbers of transition metals in half-cell systems.…”
Section: Current Progress On Layered Na X Momentioning
confidence: 99%
“…[103] A quaternary transition metal oxide, Na [ (Figure 3d), because it benefits from the synergetic effects toward high capacity induced by Fe in its composition and the structural stabilization induced by Co substitution. [104] Na x MO 2 composites with mixed phase may possess unprecedented features. [111][112][113][114][115] Combining the characteristics of P2-and P3-phases and the highly reversible structural evolution from P2/P3 to P2/OP4, P2-/P3-Na 0.7 Li 0.06 Mg 0.06 Ni 0.22 Mn 0.67 O 2 was able to deliver a high reversible capacity of 119 mAh g −1 and a high operating voltage of 3.53 V with a superior initial Coulombic efficiency of 94.8%.…”
Section: Current Progress On Layered Na X Momentioning
confidence: 99%
“…Comparison among capacity and average voltage of selected metal oxide cathodes for SIBs with energy density curves superimposed. [59,62,69,70,84,101,107,121,125,126,[129][130][131][132][133][134][135]137,140,143,146,148,151,153,159,161]a) Data based on 0.2 C; b) data based on 0.5 C; and all others are based on 0.1 C as reported in references. [196] More and more researches on layered Na x MO 2 synthesized by industrially feasible methods (solidstate or coprecipitation) with favorable properties and commercial availability is on the way, and their successful report indicates that the group of layered transition metal oxides can [196] a) The capacity was calculated based on the mass of the positive material; b) The capacity was calculated based on the mass of the negative material; TEGDME, tetraethylene glycol dimethyl ether; rGO, reduced graphene oxide; CNT, carbon nanotube; NaHBDC, monosodium terephthalate; NaTFSA, sodium bis(trifluoromethylsulfonyl)amide.…”
Section: Full Cellsmentioning
confidence: 99%
“…Comparison among capacity and average voltage of selected metal oxide cathodes for SIBs with energy density curves superimposed . a) Data based on 0.2 C; b) data based on 0.5 C; and all others are based on 0.1 C as reported in references.…”
Section: Transition Metal Oxide Cathodes For Sodium Ion Storagementioning
confidence: 99%